RESOURCE MANAGEMENT TOOLKIT OF INDUSTRIAL ENTERPRISES (Development Service Industry Management, 2024)
In the study, the focus of the scientific discourse is on aspects of the formation and effective use of resource provision of industrial enterprises. The relevance of the problem of resource management, in particular financial, intellectual and personnel, material and technical, technical and technological, investment, is characterized. Based on these principles, the purpose of the study is to generalize the theoretical and methodological principles and improve practical recommendations for the formation of the toolkit of the resource management mechanism of industrial enterprises. A mechanism with an appropriate set of its elements has been developed and tools for effective resource management of industrial enterprises have been defined. The structure of resource provision of the subject of the real sector of the economy is determined. A number of conceptual provisions on the rational formation and effective management of resource potential in business have been formulated. It is shown that industrial enterprises in the course of their functioning (starting with the adjustment of production and economic processes and ending with the sale of competitive products and reproduction of production operations) attract and rationally use a wide range of resources. The leading groups of resource provision of industrial enterprises include: economic and functional resources, as well as elements of innovative, competitive, marketing and sales, organizational and managerial, commercial and other components of the resource potential of business. It has been proven that industrial enterprises face two groups of tasks: (1) rational formation and (2) effective use and reproduction of resources. The tools of the resource management mechanism of industrial enterprises are defined, namely: the formation of a full-fledged and rational (in terms of sources of financing and use) resource provision of the production process for the implementation of the production program and the plan of strategic development of production; formation of resource support for processes of innovation and technological modernization of the industrial and economic complex, strengthening the technological competitiveness of products and enterprises; effective use of intellectual and personnel and scientific and technical support; development of the resource support system for development and market introduction of new samples of competitive products; digitization of business processes and the growing role of IT support for production activities and marketing and communication processes; accumulation of the resource base of access to foreign markets, integration of the industrial enterprise into global networks of distribution of industrial products.
Keywords: resources; resource provision